Fluvoxamina: profilo farmacoeconomico - Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2001)
In this study we mean to outline a brief pharmacoeconomic review of fluvoxamine, considering only its antidepressant use. Essential objective is to highlight all the variables of cost effectiveness, tolerance and safety that can lead some types of differential costs. This study analyses the epidemiology and the economic burden of depression and a pharmacoeconomic profile of fluvoxamine, with its characteristics of effectiveness, tolerance, safety and handiness. The pharmacoeconomic evaluation is conducted according to the cost minimization analysis (CMA), considering fluvoxamine, Selective Serotonine Reuptake Inhibitors (SSRI) and antidepressant tricycic as native treatments. Fluvoxamine differs from the others SSRI far the purchase cost and it’s more convenient than the antidepressant tricycic treatment, especially for long term therapy. Economic benefits can be distributed in a balanced way between the Italian national healthcare system (NACS), the society and the patients.